Penerapan Metode Service Quality untuk Mengetahui Kualitas Pelayanan Kantor Desa Sambirejo Timur Berbasis Web - Syauqi, Ahmad; Rini Oktari Batubara (TAMIKA: Jurnal Tugas Akhir Manajemen Informatika & Komputerisasi Akuntansi, 2025)
Sambirejo Timur Village, Percut Sei Tuan District, Deli Serdang Regency, North Sumatra Province, was established on June 15, 1999. Services at the Sambirejo Timur Village Office begin with receiving visitors who come for various administrative purposes. The purpose of the study is to ensure that all village administrative activities are recorded neatly, and to facilitate supervision and evaluation of Service Quality. The procedures carried out are expected to create a transparent and accountable environment in every service to the people of Sambirejo Timur Village. The research problem that occurred was that there were complaints from the community regarding the services provided at the Village Office, but the delivery was not given directly through the criticism and suggestion box, but through expressions from the surrounding community. The research method used in this study uses the application of the Service Quality method to determine the quality of service at the Sambirejo Timur Village Office. The results of this study will be in the form of the application of the Service Quality method to determine the quality of service at the Sambirejo Timur Village Office which is made in the form of a web application. The contribution of this study is to use the application of the Service Quality method based on digitalization/web at one of the agencies, namely the Sambirejo Timur Village Office.